The mediating role of financial behavior on business performance with human and spiritual capital - Ratnawati, Ratnawati; Rokhman, M. Taufiq Noor; Nastiti, Ratna Dwi; Prahoro, Alfedro Putut (JAS (Jurnal Akuntansi Syariah), 2025)
Purpose – This study aimed to analyze the influence of human capital, spiritual capital, and financial behavior on business performance mediated by the financial behavior of fisherwomen at the fish auction site in Situbondo regency. Method – This study uses a quantitative approach with primary data in the form of a questionnaire. The sample in this study was 66 members of the fisherwomen’s association at the fish auction place in Situbondo regency, using the census sampling technique. The analysis tool used is a structural equation model with partial least squares and a mediation test using Sobel. Findings – The study's results explain that human capital, spiritual capital, and financial behavior positively affect business performance. Human capital and spiritual capital have a direct significant effect on financial behavior. Financial behavior can mediate human and spiritual capital's effect on business performance. Implications – This study contributes to resource-based theory with Intangible assets on human and spiritual capital. Practically related agencies of Situbondo regency and the marine and fisheries agency pay attention to fisherwomen in improving business performance with a focus on how financial behavior is supported by human capital and spiritual capital.